NUEVAS SINONIMIAS DE TAQUINIDOS CHILENOS (Acta Entomológica Chilena, 2022)
lielioprosopa finita Reinhard, 1964, is nolhing elsc than an anomalous male of Spanipalpusanstralis Townsend, 1928, wilhout ocellar bristles, while Eithelioprosopa pactilis Reinhard, 1964, isagain an anomalous male of Chiloepalpns aurens (Aldrich), 1926 & 1934 with ocellar bristles anddiscals in the intermedíate segments of the abdomen, this latler condition already mentioned by Dr.Aldrich (1934) as alypical in the gcnus. Both species come from Central Chile and the types aredepositcd at the California Academy of Sciences, San Francisco, California, where they werecxamincd by the author May 1974.